Elaboration of an index to measure the competencies of the managerial management of the director personnel of the Office of the Ombusdman of Republic of the Costa Rica, 2023 (National Administration Journal, 2023)
This article presents the results of an investigation whose purpose, in a first stage, was to design and elaborate an index for the measurement of the management skills of the directing staff of the defense areas of the Ombudsman's Office of the Republic of Costa Rica for the year 2023. The measurement is carried out from the perspective of subordinate professional personnel in each defense department. The index integrates the variables of leadership, teamwork, communication, forecasting and problem solving, for which a series of Likert scale items was developed to be applied to the personnel of the different departments. Likewise, each variable that makes up the index is broken down into dimensions and these, in turn, into indicators. The proposal corresponds to the first stage of the investigation; so that the second stage will correspond to the application of the questionnaire presented here in a pilot test whose results will allow the relevance of the items and the available weights provided by a panel of experts to be evaluated using statistical methods.
Keywords: decision making; human resources management; public administration; management indicators; work environment